Fast and Effective Route for Removing Methylene Blue from Aqueous Solution by Using Red Mud-Activated Graphite Composites - Ha Xuan Linh; Ngo Thi Thu; Tran Quoc Toan; Do Tra Huong; Bui Thanh Giang; Huynh Ky Phuong Ha; Hong-Tham T. Nguyen; N. T. K. Chung; Tri Khoa Nguyen; Nguyen Thanh Hai (Journal of Chemistry)
In this work, the mixture of red mud slurry and inorganic salt ((NH4)2SO4) has been used as an electrolyte for electrochemical activation of graphite. The red mud-activated graphite composite was then used as an adsorbent for removing methylene blue from aqueous solution by the batch method. The effect of pH, contact time, adsorbent dosage, and the initial concentration of methylene blue was investigated. The optimal condition was found at pH 6, contact time 120 min, and amount of adsorbent 1 mg/L. The maximum adsorption capacity was found to be 89.28 mg/g based on the Langmuir isotherm equation, suggesting that the red mud-activated graphite composite is a very potential adsorbent for removing methylene blue and is also used in other coloured wastewater treatments.